DELINEATING STUDENTS’ ENGAGEMENT BASED ON LECTURER’S TEACHING STRATEGIES IN LISTENING COURSE - Hustiana; Ahyadi; Asdar (Univeristas Islam Negeri (UIN) Alauddin Makassar, 2022)
This study delineated the lecturer’s teaching strategies in listening for general communication course and described the impacts of those strategies in listening for general communication course toward the students’ engagement in the class. The participants were the first semester students in English Education Department, Faculty of Teacher Training and Education, Universitas Sulawesi Barat that consisted of five classes which contained of 135 students. While the lecture became a part of the reserch process itself. The technique of data collecting consisted of doing observation in learning process and also giving open ended questionnaire for the students. While technique of data analysis consist of transcribing data from recorded classroom observation and open ended question into written text. In brief, it could be concluded that in this class, the leacture applied two types teaching strategies namely autocratic style and permissive style. In autocratic style the lecture applied lecturing strategy and in permissive style the lecture applied Question answer strategy, Group discussion, Role playing, and Independent study. Based on the research, the most effective strategies in listening for general communication course were question answer strategy, role playing, and Independent study because those strategies made the students contributed in learning process like asking a question, giving opinion, tutoring their friends, and giving feedback weather in written or sopken form after listening the audio. While lecturing and group discussion were not appropriate for listening course because the students be more passive with less engagement. Therefore, it was suggested for the lecture to modify the way in using lecturing and group discussion strategies in listening for general communication course, in order those strategy be more efective in the other class session.